Специфіка трансфесійної готовності студентів факультетів мистецтв до продуктивно-творчої діяльності: науковий аналіз проблеми - Лі На; Li Na (Видавництво «Код», 2025)
Резюме. У статті досліджується проблема трансфесійної готовності студентів факультетів мистецтв до продуктивно-творчої діяльності в сучасному музичноосвітньому просторі. Визначено, що сучасний музично-освітній простір дедалі частіше функціонує на засадах міждисциплінарності, інноваційності та креативності, що зумовлює потребу підготовки конкурентоспроможних фахівців нової генерації, здатних інтегрувати художньо-виконавські, педагогічні, проєктно-організаційні та комунікативні компетентності для реалізації продуктивно-творчої діяльності.

Abstract. The article investigates the problem of transfaith readiness of students of faculties of arts for productive and creative activity in the modern music and educational space. It is determined that the modern music and educational space increasingly functions on the principles of interdisciplinarity, innovation and creativity, which determines the need to train competitive specialists of the new generation, capable of integrating artistic and performing, pedagogical, design and organizational and communicative competencies for the implementation of productive and creative activity. The conducted thorough analysis of scientific sources on the selected problem opens the way to specifying the main scientific directions that are directly related to the problem of forming transfaith readiness of future teachers of music for productive and creative activity, namely: theoretical developments dedicated to the disclosure of transfaith guidelines in the system of higher art education; research on the problem of readiness for professional activity in the psychological and pedagogical aspect; strengthening the transdisciplinary direction, transfascial orientation of professional training of students of faculties of arts, which allows to determine the essence of transfascial readiness of students for productive and creative activity. It is determined that for a modern specialist of an artistic profile it is important not only to master their own direction, but also to be able to interact with other types of art, technologies, audiences and formats of a cultural product. The significance of transfascial readiness of students of faculties of arts for productive and creative activity, which consists in the ability of a future specialist to integrate knowledge, skills, individual creative qualities and artistic and practical experience from various artistic and related fields for the effective implementation of professional activity, which requires constant rethinking, innovation and creativity, is proven.
Specificity of transfaith readiness of students of faculties of arts for productive and creative activity: scientific analysis of the problem
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-17?authuser=0
Keywords: готовність; психологічна готовність; трансфесійна готовність; студенти факультетів мистецтв; продуктивно-творча діяльність; мистецько-освітній простір